The Birth of National Parks: Culture and Nature in Visiting the Wilderness in the United States (1920-1940). - Bacheller, Micah; Dutra e Silva, Sandro (História Revista, 2017)
This paper aims to analyze the birth of the National Park System and Service in the United States, as well as the factors related to the increase in visitors to the Parks between 1920 and 1940. The work is based on the theoretical and methodological assumptions of Environmental history, focusing on the history of nature conservation and the creation of protected areas. It delves into the elements of regulation of the services related to national Parks, and the institutionalization of practices of visitation in that period. The central arguments of this article are: the dissemination of natural beauty in the United States, creation of a positive idea about frequency and visitation to parks, and nature conservation areas in the early twentieth century. Also, from the history of the creation of the services and management systems of the National Parks in President Wilson´s tenure (1913 - 1921), it is possible to identify the relationship between society, culture and nature in this historical context.